Observable Versus Unobservable Contracts in Duopolistic Competition - Ayu Sasni Munte; Arie Kawulur (AIBPM Publisher, 2022)
One upstream and two downstream firms are involved in a vertically related industry. Under observable contracts, firms are aware of both their own and their rival's input prices. However, under an unobservable contract, firms only know their own input price and are unaware of their rival’s input price. We demonstrate both vertical separation and vertical integration in the two contracts. We focus on two methods: linear tariffs and two-part tariffs. With linear tariffs and asymmetric costs under both observable contracts and unobservable contracts, vertical integration increases consumer surplus and social welfare. With separation linear tariffs and asymmetric costs, consumer surplus (social welfare) is lower (higher) under observable contracts than under unobservable contracts. With two-part tariffs, vertical integration does not affect (decreases) both consumer surplus and social welfare under observable contracts (under unobservable contracts). Under separation two-part tariffs, consumer surplus and social welfare are lower under observable two-part tariffs than under unobservable ones. Keywords: Observable Contracts, Unobservable Contracts, Duopolistic Competition